Mechanism and management of angle closure in uveitis. Issue 2 (March 2015) - Sng, Chelvin C.A.; Barton, Keith
Abstract : Purpose of review: To summarize the multiple mechanisms responsible for angle closure in uveitis and to outline the management principles and treatment modalities. Recent findings: Angle closure in uveitis is a heterogeneous disease with multiple mechanisms. Recent advances in anterior segment imaging have provided insights into the mechanisms of angle closure in uveitis. Uveitic eyes with angle closure from pupil block require surgical iridectomy with mobilization of the peripheral iris and viscogoniosynechiolysis of both posterior synechiae and peripheral anterior synechiae. Systemic conditions associated with uveitis can result in anterior displacement of the iris–lens diaphragm, and present as acute angle closure. Pupil block is not the predominant mechanism in these eyes, and management is primarily medical. Data are limited on the optimal treatment of angle closure in uveitis, and the role of glaucoma filtration surgery, cataract extraction, minimally invasive glaucoma surgery and newer modalities of cycloablation require evaluation. Summary: The management of angle closure in uveitis should adhere to the principles of managing both uveitic glaucoma and angle closure. Identification of the mechanism of angle closure in uveitic eyes may enable treatment to be targeted at the responsible mechanism.